Recent Progress in Electrolytes for Zn–Air Batteries - Chen, Peng; Zhang, Keyi; Tang, Dejian; Liu, Weilin; Meng, Fancheng; Huang, Qiuwei; Liu, Jiehua (Frontiers in Chemistry, 2020)
Zn–air battery is considered as one of the most promising candidates for next-generation batteries for energy storage due to safety, high energy density, and low cost. There are many challenges in electrolytes for developing high-performance rechargeable Zn–air cells as well as electrocatalysts. An electrolyte is the crucial part of the rechargeable Zn–air batteries that determine their capacity, cycling stability and lifetime. This paper reviews the most recent progress in designing and fabricating electrolytes in aqueous and flexible Zn–air batteries. The discussion on the surface reaction relationships was covered between air-catalyst-electrolyte and electrolyte-zinc reaction mechanism. We highlight the recent developments of three different electrolytes in zinc-air battery: aqueous electrolyte, room-temperature ionic liquid, and quasi-solid flexible electrolyte. Furthermore, the general perspective is proposed for designing and fabricating electrolytes to improve the performance and prolong the lifetime of Zn–air batteries.